ANTIBIOTIC COMPOUND FROM MARINE ACTINOMYCETES (Streptomyces sp A11): ISOLATION AND STRUCTURE ELUCIDATON - Rofiq Sunaryanto; Bambang Marwoto; Tun Tedja Irawadi; Zainal Alim Mas’ud; Liesbetini Hartoto (Universitas Gadjah Mada, 2010)
Purification and structure elucidation of antibiotic produced by marine actinomycetes (Streptomyces sp A11) was conducted. Production of antibiotic was carried out by liquid fermentation using yeast and peptone medium for 5 days fermentation. Purification of antibiotic was carried out by silica gel 60 (Merck, 0.063-0.200 mm) column chromatography and preparative HPLC. Structure elucidation was carried out using ESI-MS, 1H NMR, 13C NMR, DEPT 13C NMR, and FTIR. This antibiotic was identified as cyclo (tyrosyl-prolyl) / (C14H16N2O3). This antibiotic had biological activity to Escherichia coli ATCC 25922, Staphylococcus aureus ATCC25923, Bacillus subtilis ATCC 66923, Pseudomonas aeruginosa ATCC27853, and produced by extracellular secretion.